THE SYNTAXONOMY ANO SYNGENESIS OF THE ELYNOSESLERIETEA BR.-BL. 1948 IN THE BALKAN PENINSULA - REDZIC, S. (Annali di Botanica, 2003)
High mountain vegetation on calcareous geological foundation is prevalent in the alpine and subalpine belts of mountains on the Balkan peninsula. The class ElYf1o-Seslerielea is represented in alpine and subalpine communities of meadows and pastures in these communities. species from Dinaric, Balkan, Illyrian, and the south-eastern European floral element play dominant role. In the investigation area, the class is differentiated into the following orders: Seslerietalia juncifoliae (=tenuifoliae) Horvat 1930 with alliances Seslerion juncifoliae (=tenuifoliae) Horvat 1930 in alpine belts and Festucion bosniacae (=pungentis) Horvat 1930 in the subalpine belts and Festudon paniculatae calcicolum (Redzic, Lakusic et al.. 1984) Redzic in North-western part; OnobrychydoSeslerietalia Horvat 1949 with alliances Onobrycho-Festucion Horvat 1936, Festuco-Knaution longifoliae Horvat 1949, Edraiantho-Seslerion Horvat 1949, Seslerion rigidae Zolyomy 1939 and Seslerio-Festucion xanthinae Horvat 1949 in the eastern and southern part; Order Crepidetalia dinaricae (=urumovii) Lakusic 1966 with al1iances Campanulion linifolii Lakusic.: 1964, Festucion pseudoxanthinae Lakusic 1968. Oxytropidion dinaricae (=urumovii) Lakusic 1966 in the south-eastern Dinaric Alps; arder Edraintho-Seslerietalia robustae Orda nov prov. with alliances Seslerion robustae (Lakusic et al. 19R2) and Seslerio-Edraianthion pumilii Redzic all. nova prov. in the coastal side of oro-mediterranean region of Balkans.